2015
DOI: 10.1155/2015/792016
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Ozone Administration Reduces Intestinal Mucosa Injury Induced by Intestinal Ischemia‐Reperfusion in the Rat

Abstract: Objectives. Intestinal ischemia-reperfusion injury is associated with mucosal damage and has a high rate of mortality. Various beneficial effects of ozone have been shown. The aim of the present study was to show the effects of ozone in ischemia reperfusion model in intestine. Material and Method. Twenty eight Wistar rats were randomized into four groups with seven rats in each group. Control group was administered serum physiologic (SF) intraperitoneally (ip) for five days. Ozone group was administered 1 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 27 publications
3
24
3
Order By: Relevance
“…Ozone regulates cellular antioxidant systems, such as SOD, glutathione, and enzymatic reactions, preparing the host to confront the pathophysiologic conditions regulated by oxidative stress (Kesik et al, 2009). In this study, we demonstrated that ozone significantly increased some key antioxidant parameters, such as SOD, GSH‐Px, and CAT, which was consistent with the previous reports (Rodriguez et al, 2009; Onal et al, 2015). The cell injury caused by oxidative stress could increase MDA, and significant decrease of MDA after ozone treatment indicated that the mitochondrial oxidative damage induced by I/R injury was markedly reduced by ozone.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Ozone regulates cellular antioxidant systems, such as SOD, glutathione, and enzymatic reactions, preparing the host to confront the pathophysiologic conditions regulated by oxidative stress (Kesik et al, 2009). In this study, we demonstrated that ozone significantly increased some key antioxidant parameters, such as SOD, GSH‐Px, and CAT, which was consistent with the previous reports (Rodriguez et al, 2009; Onal et al, 2015). The cell injury caused by oxidative stress could increase MDA, and significant decrease of MDA after ozone treatment indicated that the mitochondrial oxidative damage induced by I/R injury was markedly reduced by ozone.…”
Section: Discussionsupporting
confidence: 93%
“…It can oxidize many microorganisms and its related toxins at different rates, and prepare the host to face physiopathological events regulated by reactive oxygen species (ROS) (Onal et al, 2015). Ozone has been proved to protect several organs in the animal models of I/R injury (Chen et al, 2008; Onal et al, 2015). However, it is not clear how ozone prevents or attenuates cerebral I/R injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the inflammatory response, there are changes in the ratio of leukocytes in circulation. Hypoxia occurring in situations of spinal cord ischemia may be seen biochemically due to acidosis, free radical damage and membrane disruption [15]. Medical ozone is a chemical agent that consists of three oxygen atoms and has antioxidant, angiogenic and vasodilator effects.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were examined and scored by pathologists blinded to each other's observations. Pathological damage to the intestinal tissues in each group was analyzed semiquantitatively: 0 indicated normal mucosal villi; 1 indicated the subepithelial space above the villi; 2 indicated moderate elevation of the superior cortex of the lamina propria; 3 indicated large epithelial uplift on both sides of the villi (a few tips may fall off); 4 indicated villus shedding, lamina propria exposure, and telangiectasia; and 5 indicated lamina propria calving, hemorrhage, and ulcer [20][21][22].…”
Section: Histologymentioning
confidence: 99%